Vremâ i âzyk: sistemy ocenki - Dement’ev, Vadim V. (Stylistyka, 2021)
The value systems are different in different languages. In diachronia these systems vary at a high degree. Changes in this sphere may be connected either with single value lexemes, lexical-semantic groups or much morę generał value systems. This article is devoted to researching some of these whole-language value systems. Changes in the mo- ral-ethic sphere of oppositiveness and continuality in Russian, English and some other European languages are analyzed. Much attention of the author is devoted to the opposi- tion “personal ~ impersonal” in the Russian language as well as to its correspondence to other languages.